Assessment of a baloxavir marboxil treatment protocol for high pathogenicity avian influenza in Okinawa Rails, an endangered species endemic to Japan - Mariko Miki; Yo Shimazu; Ryo Daniel Obara; Takashi Nagamine; Yumiko Nakaya; Yoshinori Ikenaka; Hiromi Osaki; Takashi Kimura; Takahiro Hiono; Norikazu Isoda; Takao Shishido; Yoshihiro Sakoda (PLoS ONE, 2026)
High pathogenicity avian influenza (HPAI) is a highly infectious and lethal disease of birds that causes systemic symptoms and has been spreading globally, including in Japan. The Okinawa rail ( Hypotaenidia okinawae ), a flightless bird endemic to Japan, is classified as an endangered species on the Red List. In 2004, the Ministry of the Environment of Japan began implementing a conservation breeding program for Okinawa rails, focusing on maintaining the species’ genetic diversity, captive breeding, and reintroduction to the wild. Given the potential for significant losses due to HPAI in Okinawa rails, the establishment of a treatment protocol as a preparedness measure is essential. The aim of this study was to determine an appropriate treatment method for HPAI in Okinawa rails using baloxavir marboxil (BXM), a drug shown to be effective in an avian laboratory model of HPAI virus infection. Single oral administration of BXM at 2.5 or 12.5 mg/kg did not produce plasma concentrations sufficient to achieve the expected therapeutic efficacy. Therefore, oral administration was deemed inadequate for generating the desired pharmacological effects. Consequently, subcutaneous administration of BXM to Okinawa rails at a dose of 2.5 or 7.5 mg/kg was explored as an alternative protocol, which resulted in higher systemic exposure compared with oral administration. Furthermore, plasma concentrations were maintained at therapeutically relevant levels up to 24 hours after subcutaneous administration at 7.5 mg/kg, with mild and reversible injection site irritation the main adverse effect. Based on these results, subcutaneous administration of BXM is proposed as a viable treatment protocol for HPAI in the conservation of endangered Okinawa rails.